D’un paratexte, l’autre : les métamorphoses pastorales de Jean Mairet - Jean-Pierre van Elslande (Les Dossiers du GRIHL)
This article examines how the three first plays published by Jean Mairet around 1630 (Chriséide et Arimant; La Sylvie and La Silvanire) display very different forms of paratexts, all of which contribute to the promotion of a young playwright fully aware of his role in the active debates surrounding the rules of dramatic composition, but also highly concerned about the rise of absolutism.